2017
DOI: 10.1158/1078-0432.ccr-17-0944
|View full text |Cite
|
Sign up to set email alerts
|

Local Adjuvant Treatment with Low-Dose CpG-B Offers Durable Protection against Disease Recurrence in Clinical Stage I–II Melanoma: Data from Two Randomized Phase II Trials

Abstract: Although risk of recurrence after surgical removal of clinical stage I-II melanoma is considerable, there is no adjuvant therapy with proven efficacy. Here, we provide clinical evidence that a local conditioning regimen, aimed at immunologic arming of the tumor-draining lymph nodes, may provide durable protection against disease recurrence (median follow-up, 88.8 months). In two randomized phase II trials, patients, diagnosed with stage I-II melanoma after excision of the primary tumor, received local injectio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 28 publications
(56 reference statements)
2
43
0
Order By: Relevance
“…In line with their reported functional abilities (14), frequencies of in vivo recruited and matured LNresident cDC correlated with increased ex vivo cross-presenting capacity of SLN suspensions (12). We have followed patients participating in these randomized and placebo controlled trials, and have found prolonged melanoma-specific survival and systemic tumor control in groups treated with CpG-B (43).…”
Section: Discussionsupporting
confidence: 57%
“…In line with their reported functional abilities (14), frequencies of in vivo recruited and matured LNresident cDC correlated with increased ex vivo cross-presenting capacity of SLN suspensions (12). We have followed patients participating in these randomized and placebo controlled trials, and have found prolonged melanoma-specific survival and systemic tumor control in groups treated with CpG-B (43).…”
Section: Discussionsupporting
confidence: 57%
“…Our prior studies have demonstrated that immune mechanisms can control minimal residual disease following surgical resection in preclinical models, and that the addition of systemic immunotherapy can enhance local control (3). Moreover, in melanoma we demonstrated clinical immune control of distant metastasis by local injections of CpG after surgical removal of the primary tumor and 1 week prior to the sentinel lymph node procedure (4). Thus, the ability to enhance tumor-specific adaptive immune responses at the time of the initial procedure may be valuable for control of residual microscopic disease, as well as distant tumor deposits (3,5,6).…”
Section: Introductionmentioning
confidence: 73%
“…The potential of TDLNs is demonstrated in the clinical study of Koster et al in which stage I and II melanoma patients were treated with immune-stim-ulating TLR9 agonist CpG in the scar of tumor resection, before TDLN resection. Patients displayed stronger tumor-specific immune responses and longer recurrence-free survival than placebo-injected patients (22).…”
Section: Discussionmentioning
confidence: 93%